Legal Protection of Children's Survival Rights in the Perspective of the Principles of Justice - Utari Dewi Fatimah; Nia Kania Winayanti (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Every child has the right to protection by parents, family, society, and the state, and the right to survival is the responsibility and obligation of parents, government and the state, in maintaining and non-discrimination of children's rights to life. descriptive analytical research, a research that describes and describes, the facts as an object or an event that occurs in connection with the legal protection of children's survival. The research was conducted using a normative juridical method. The right to life is a human right, an absolute right that is inherent in everyone and is included in the category of non-derogable rights, namely rights that cannot be reduced under any circumstances